Mediating effect of job satisfaction and moderating effect of employment status on relationship between core self-evaluation and work ability among employees with disability in Malaysia - Lavasani, Seyed Sobhan (2015)
This study was designed to extend the holistic multidimensional model of work ability by including the direct relationship between core self-evaluation and work ability as well as the indirect relationship through the mediating effect of general and specific facets of job satisfaction among employees with disability in Malaysia.The studies on work ability were developed by Finnish researchers of the Finnish Institute of Occupational Health-Helsinki-Finland since the beginning of the 1980‘s to prevent the inability to work across aging workers and have been extended to other non-aged employees in all groups of employees across many countries of the world. However studies on the predictors of work ability are still ongoing. Furthermore, Limited studies showed that there has been not enough attention paid to work ability of some particular employees like employees with disability. In this regard a conceptual model was developed to examine the relationship between core self-evaluation of employees with disability and their work ability. In this model the general and specific facets of job satisfaction was considered to mediate the relationship between core self-evaluation and work ability as well as the employment status was considered to moderate this relationship. In order to meet the objectives of the study a cross-sectional, correlational survey design was used and standard self-administered questionnaires were used to gather data among 275 employees with disability who were randomly selected from members of disability Non-government Organizations (NGOs) in 8 Malaysian state. Descriptive analysis and Structural Equation Modeling (SEM ) was conducted for data analysis. The descriptive findings of the study revealed that most of the respondents reported moderate (49.1%) and high (43.6%) levels of core self evaluation. Majority of the respondents also reported high job satisfaction in general (70%) and most of them expressed that they were satisfied with work itself (74.5%), with coworkers (78.9%) and with supervisions(76%). More than half of the respondents reported high satisfaction with the pay (58.9%) while above half of respondents were not satisfied with opportunities for promotion (53.5%). Results also showed that 29.5% of respondents perceived their work ability as poor, 32.08% perceived it as moderate,28.7% perceived it as good and just 6.5% perceived excellent level of work ability. The results of the Structural Equation Model analysis indicated that there is a positive significant relationship between core self evaluation and work ability. The results also revealed that although there is a positive significant association between job satisfactions in general and work ability but among specific facets of job satisfaction, only satisfaction with coworker and supervision have positive and significant relationship with work ability. The results also unveiled that among job satisfaction in general and specific facets of job satisfaction just satisfaction with coworker and satisfaction with supervision mediated the relationship between core self-evaluation and work ability. Finally, the results revealed that employment status moderated the relationship between core self-evaluation and work ability. This study provided a unique contribution to research by developing a framework for future researches by combining empirically grounded findings together with theoretical explanation from the literature. This study also highlighted some implication and recommendations for policy and practice toward the improvement of employees with disability‘s work ability.